(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The field experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during Aman season of 2014 to study the influence of different levels of zinc applied from two sources on the yield and Zn uptake of BRRI dhan49. The soil was silt loam in texture having pH 6.8, organic matter 2.72%, total N 0.151 %, available P 4.00 mg kg-1, available K 0.08 cmol kg-1, available S 15.9 mg kg-1 and available Zn 0.90 mg kg-1. The experiment was laid out in a randomized complete block design with three replications. There were seven treatments with different rates of Zn viz. T1: Zn0, T2: Zn1 as ZnO, T3: Zn2 as ZnO, T4: Zn3 as ZnO, T5: Zn1 as ZnSO4, T6: Zn2 as ZnSO4, and T7: Zn3 as ZnSO4 where 0, 1, 2 and 3 represent the rate of Zn in kg ha-1. Recommended doses of N, P, K and S fertilizers were added to all plots and they were used in the form of urea, TSP, MoP and gypsum, respectively. Addition of Zn had significant effect on the grain and straw yields of BRRI dhan49. Application of ZnO at 3 kg ha-1 (T4) produced the highest grain (5294 kg ha-1) and straw (6567 kg ha-1) yields. The control treatment (Zn0) produced the lowest grain (3183 kg ha-1) and straw (3614 kg ha-1) yields. The other plant parameters such as panicle length, tillers hill-1 and grains panicle-1, but not plant height and 1000-grain weight were also influenced significantly by the application of zinc. Zn concentration and uptake by BRRI dhan49 were also influenced by the addition of Zn. The total Zn uptake by the BRRI dhan49 varied from 173 g ha-1 in control to 353 g ha-1 in T4. Thus, results suggest that application of ZnO @ 3 kg ha-1 along with NPKS at recommended rates needs to be applied for achieving higher yield of aman rice in Old Brahmaputra Floodplain Soil. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 230-234